A reflective multiple case study approach to understanding partner relationships within the context of community engagement at Rhodes University - Bobo, Azola Benita Dorothea (Rhodes University, Faculty of Humanities, Department of Psychology)
Using a social constructivist approach, within the social action model of community psychology, this research interrogates the features of successful community engagement partnerships that exist within the context of higher education. It draws on the co-management model that the Rhodes University Community Engagement (RUCE) division proposes, where partnerships are seen to be mutually beneficial. This research further interrogates whether the principles of community engagement that RUCE propose play out in reality, and whether systems of power are deconstructed, in working towards more equitable engagements. Drawing on the Early Childhood Development (ECD) Residence Programme for case studies, this research used a reflective multiple case study design in attempting to answer the research question. Four partner groups (i.e., 4 community partners and 4 community engagement representatives) were selected for this research. Each participant was interviewed twice (with a 6-month time gap) and also participated in two focus group discussions. Thematic analysis was used to analyse the findings. In taking a social justice approach, it can be argued that RUCE has made strides towards forming collaborative partnerships based on the ethics of ubuntu and aspects of transformative learning, which may lead to the decolonisation of higher education. However, critical engagement with the research findings suggests that in many cases the principles that RUCE propose are aspirational. More work needs to be done with both students and community partners to develop the kinds of partnerships that RUCE aspires to. This research provides valuable insight into how carefully managed community engagement partnerships in higher education have the potential to contribute to the transformation agenda of higher education institutions, while promoting equitable societies.
Keywords: Community development -- South Africa -- Makhanda; Community and college -- South Africa -- Makhanda; Community psychology -- South Africa -- Makhanda; Decolonization -- South Africa; Social action -- South Africa -- Makhanda; Transformative learning -- South Africa -- Makhanda; Rhodes University; Rhodes University Community Engagement (RUCE)